Analisis Kelayakan Bisnis Kedai Kopi (Studi Kasus Pada Agrowisata N8 Malabar, Pangalengan, Kabupaten Bandung) - Nabila Ananda Putri; Zumi Saidah; Dika Supyandi; Lucyana Trimo (Journal of Food System & Agribusiness, 2019)
The increasing trend of coffee consumption leads to Agrowisata N8’s plan to open a coffee shop in their lodging area as an addition to their facilities and asset utilization that are expected to provide economic value. The aim of this study is to obtain a feasibility analysis of a coffee shop that located in Agrowisata N8 Malabar with a qualitative research method and a case study approach. Data collection techniques carried out in the form of library research, interviews, observation and documentation. This feasibility study are observed from legal aspect, market and marketing aspect, environmental aspect, management and human resources aspect, technical and technological aspect and financial aspects with the calculation of the feasibility of investment such as NPV, IRR, Net B/C and Payback Period. The results showed that based on the non-financial aspect, this coffee shop is feasible to run. Financial analysis of Agrowisata N8 coffee shop shows an NPV value of Rp. 82,929,169, an IRR value of 49.51%, a Net B / C of 1.78 and a payback period of 2 years and 4 months. Keywords: Coffee Shop, Feasibility Study, Malabar